PELATIHAN PEMBUATAN VIRGIN COCONUT OIL DAN KECAP MANIS DARI KELAPA DI KECAMATAN MOROTAI JAYA KABUPATEN PULAU MOROTAI - Yuliana Wattimena, Anna; Ivonne Nendissa, Jeanne; G. I. Kembauw, Marthina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2022)
Coconut is a commodity that has a high economic value if it is used every part of it into a type of derivative product for sale. Assistance in making VCO and soy sauce is one of the community service activities from the Ambon Community Training Center with the Pattimura University Innovation Center. This activity was carried out as a way to provide solutions for the people of Morotai Jaya with the hope that it could help increase the economic value of coconut and increase people's income on a household scale. The main purpose of community service activities with the theme